Jump Analysis Based on Player Specialization in Men’s Volleyball Matches - Nurhudin, Muhammad Qoirul; Jotikasthira, Nuttapong (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to analyze the jumping activity of male volleyball players based on positional specialization during an official match in order to identify the frequency and distribution of jumps as a representation of athletes’ physical workload in competition. Methodology: This study used a descriptive qualitative design with an observational approach. Data were collected through match video recordings (YouTube) and analyzed using structured observation sheets. The subjects were male volleyball players in the Porprov VII final match. Data were processed using descriptive statistics, including frequency counts and averages. Main Findings: The results show that players performed an average of 21 jumps per set with a range of 15–29 jumps, and 5–10 jumps per rotation with an average of 7. Jumping activity varied based on player positions, where front-row players performed more jumps than back-row players during the match. Novelty/Originality of this study: This study provides a novel approach by analyzing actual jumping activity during real match conditions based on player positions and sets. It offers empirical data on physical workload, contributing to the development of more specific and evidence-based training programs aligned with real competition demands.